Analysis and spatio-temporal modelling of spatial patterns in urban systems: agglomeration, segregation and food deserts - Whiteley, Timothy D (2020)
Urban population distributions in cities can show structure such as patchy patterning that may relate to important properties such as journey times, quality of life and sustainability. In this thesis we wish to address the question of what patterns exist between and within cities, and highlight the social unsustainability of the current set up.